Five-phase space vector modulation voltage source inverter using large, medium and zero vector combination technique / Naqiuddin Razalini - Razalini, Naqiuddin (2014)
The development of power electronics toward the future is massive and leads to the application of electric drives with the number of phase greater than three such as the multi-phase inverter. This project is about to generate five-phase AC voltage waveform from the five-phase space vector modulation VSI using the combination of active (large and medium) vector with zero vector switching technique and analyzed its result by implementing the switching technique into the simulation and record the performance of the output at the load. The Low Order Harmonic (LOH) such as 3rd , 5 and 7th harmonic produce by d3-q3 subspace will be reduced by using the combination of large, medium and zero vector technique. In this project also, the implementation of hardware of five-phase voltage source inverter by interfacing using the ezDSP TMS320F2812 also will be introduced. The DSP will generate an analogue output by the coding from the MATLAB/SIMULINK in order to generate the space vector pulse width modulation for the inverter circuit. By using this five-phase source inverter hardware, the output waveform of phase voltage, line-to-line voltage and the pole voltage could be analyzed.